Long-term rowing performance development in male Olympic and World Championship medal winners compared with nonmedalists - Mäestu, J.; Lelle, R.; Mäestu, E.; Pind, R.; Vahtra, E.; Purge, P.; Mikulic, P. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was, first, to investigate individual longitudinal 2,000 m rowing ergometer performance (2,000 erg) development of world class male rowers from the beginning of their career until reaching the elite level and to compare ELITE performance development with those who did not reach podium places and, second, to provide 2,000 erg milestones for talent prediction in rowing. Individual annual 2,000 erg performances of 54 male rowers were analyzed from age 15 and throughout their career. Olympic or World Championships medal winners (ELITE; n = 11) were compared with those who did not reach international podium places. Two thousand erg increased (p = 0.05) until the age of 24 in ELITE, while plateaued earlier for less successful rowers. No differences in the rate of performance improvement were found between ELITE and lower performers (p > 0.05). At the age of 20, performance between ELITE and international level nonmedal winners reached significant difference (480.7 ± 20.9 W vs. 435.3 ± 33.9 W, respectively) and remained different onwards (p = 0.05). However, the average of the 10 best seasons cross-sectional performances of less successful rowers were significantly higher until age 18, compared with ELITE. ELITE rowers were able to improve their 2,000 erg performance to higher age; therefore, it is difficult to predict elite performers in junior rowers. Cross-sectional performances of less successful rowers may indicate temporary high-level performers, who might not be able to advance the elite level.